Reclaiming wellness: Key factors in restoring optimal well-being in the Canadian Longitudinal Study on Aging - Mabel Ho; Esme Fuller-Thomson (PLoS ONE, 2025)
Background This study examines characteristics of older adults who have regained optimal well-being at the end of the three-year study. The definition of optimal well-being used in this study refers to having adequate social support, high levels of older adults’ subjective perception of their aging process, physical health, mental health, happiness and life satisfaction and being free of limitations in Activities of Daily Living (ADLs) and Instrumental Activities of Daily Living (IADLs), disabling pain or discomfort, severe mental illness or cognitive decline in the preceding year. Methods A secondary data analysis was conducted using the first two waves of data from the comprehensive cohort of the Canadian Longitudinal Study on Aging (CLSA), a large, national, longitudinal study on aging. The sample included 8332 older adults who were not in optimal well-being at baseline and aged 60+ at time 2. Bivariate and multivariable binary logistic regression analyses were used to examine which baseline characteristics were associated with achieving optimal well-being approximately three years later. Results The prevalence of optimal well-being at time 2 was higher among respondents who, at baseline, were younger, married, physically active, not obese, non-smokers, had higher income, without sleeping problems, diabetes, arthritis, osteoporosis, and achieved at least two of the four wellness domains (i.e., physical, psychological and emotional, social, and self-rated wellness) were more likely to be in optimal well-being at time 2 than their counterparts. Conclusions Old age does not necessarily result in poor physical health, nor is a decline in well-being inevitable. Almost one in four respondents who were in less than optimal well-being at baseline regained well-being over the ensuing approximately 3 years. Further research could investigate the association between policies and programs and their support for older adults in regaining optimal well-being in later life after a period of suboptimal well-being.